TSPO is a potential independent prognostic factor associated with cellular respiration and p16 in head and neck squamous cell carcinoma - Tuominen, Sanni; Nissi, Linda; Kukkula, Antti; Routila, Johannes; Huusko, Teemu; Leivo, Ilmo; Minn, Heikki; Irjala, Heikki; Löyttyniemi, Eliisa; Ventelä, Sami; Sundvall, Maria; Grönroos, Tove J. (Frontiers in Oncology, 2023)
Background Treatment resistance and relapse are common problems in head and neck squamous cell carcinoma (HNSCC). Except for p16, no clinically accepted prognostic biomarkers are available for HNSCC. New biomarkers predictive of recurrence and survival are crucial for optimal treatment planning and patient outcome. High translocator protein (TSPO) levels have been associated with poor survival in cancer, but the role of TSPO has not been extensively evaluated in HNSCC. Materials and methods TSPO expression was determined in a large population-based tissue microarray cohort including 611 patients with HNSCC and evaluated for survival in several clinicopathological subgroups. A TCGA HNSCC cohort was used to further analyze the role of TSPO in HNSCC. Results TSPO expression was downregulated in more aggressive tumors. Low TSPO expression associated with worse 5-year survival and was an independent prognostic factor for disease-specific survival. Subgroup analyses showed that low TSPO expression associated with worse survival particularly in p16-positive oropharyngeal cancer. In silico analyses supported the prognostic role of TSPO. Cellular respiration had the highest significance in pathway analyses for genes expressed positively with TSPO. Conclusion Decreased TSPO expression associates with poor prognosis in HNSCC. TSPO is a prognostic biomarker in HNSCC to potentially guide treatment stratification especially in p16-positive oropharyngeal cancer.